Optimizing cohousing: the effect of community size on common space utilization and organizational sustainability - Milošević Pantović, Aleksandra (Arhitektura i urbanizam, 2024)
This research aims to provide a deeper understanding of the relationship between the size of cohousing communities and the distribution of common areas, applying analysis criteria such as the size, layout, and function of these spaces. The hypothesis suggests that there is an inverse correlation between community size and the percentage of common areas relative to the total surface area, meaning that larger communities have a lower percentage of common areas. The research methodology includes a review and analysis of housing community examples from various cultural and urban contexts, aiming to identify key factors that influence the organizational structures and economic sustainability of these communities. The study also examines the level of community autonomy, based on their size and complexity. The results of this research show that smaller cohousing communities have a higher percentage of common areas relative to the total surface area, while in larger communities, this percentage decreases. This relationship has significant implications for the organization, functionality, and economic sustainability of communities. The research provides new insights that can contribute to the future design and organization of cohousing communities, aiming to preserve the core values of community and cooperation, while optimizing common spaces and improving the quality of life for residents.
Keywords: cohousing communities; common spaces; community sustainability; community size; governance system